PENGARUH ORGANISASI SEKOLAH DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII MTs. DARUL ULUM KOTABARU TP. 2016/2017 - Faisal Batennie; Radiatul Adawiah (STKIP Paris Barantai, 2017)
This research is madeto find out the influence of school organization and learning style toward mathematic learning achievement. As follows: 1) To find out the influence between student activity in school organization toward mathematic learning achievement, 2) To find out the influence between learning style toward mathematic learning achievement, 3) To find out the influence between student activity in organization and learning styletoward mathematic learning achievement. The research is quantitative research which used descriptive method. The purpose of this research is giving description about the influence of student activity in school organization and learning style student toward mathematic learning achievement of eight grade student MTs. Darul Ulum Kotabaru academic year 2016/2017. The result of this research: 1) there is significant influence between student activityin organization at school toward learning achievement, 2) there is significant influence between student learning style toward learning achievement, and 3) there is significant influence between students activity in organization at school toward student learning style. Keywords: School Organization, Learning Style and Learning Achievement